Occupational Exposure Duration and Declining Peak Expiratory Flow Among Traditional Compressor Divers - Arfiyan Sukmadi; Arwan Arif Rahman (Institut Kesehatan Suaka Insan, 2026)
Despite the widespread practice of traditional compressor-assisted diving in coastal Indonesia, evidence regarding its impact on pulmonary function remains limited. This cross-sectional study examined the association between occupational exposure duration and Peak Expiratory Flow (PEF) among 57 male traditional divers in Southeast Sulawesi. Using a standardized peak flow meter and structured questionnaires, the study found a mean PEF of 472.61 ± 90.55 L/min. Simple linear regression demonstrated a significant negative association (B = -3.99; p = 0.033), indicating that each additional year of diving decreases PEF by an average of 3.99 L/min, with work duration explaining 8.0% of the PEF variation (R² = 0.080). Ultimately, longer occupational exposure significantly reduces pulmonary function, underscoring the urgent need for routine respiratory screening and community-based health monitoring for early detection of pulmonary decline in coastal maritime workers.